Multivariate Analysis in Advanced Oxidation Process - Freitas, Ana Paula Barbosa Rodrigues de; Freitas, Leandro Valim de; Samanamud, Gisella Lamas; Marins, Fernando Augusto Silva; Loures, Carla Cristina Almeida; Salman, Fatima; Santos, Túlio Lima dos; Silva, Messias Borges (IntechOpen, 2013)
None